Lucy Delap: Feminisms: A Global History - Šůsová, Kristina (Czech Journal of International Relations, 2021)
Feminism’s origins have often been framed around a limited cast of mostly white and educated foremothers, but the truth is that feminism has been and continues to be a global movement. For centuries, women from all walks of life have been mobilizing for gender justice. As the last decade has reminded even the most powerful women, there is nothing “post-feminist” about our world. And there is much to be learned from the passion and protests of the past.